On purposefulners of the mathematics course presented at the education faculty - Viruišis, Vaclovas (Lietuvos matematikos rinkinys, 1999)
While analysing the course of mathematics presented at the Education Faculty experience and observation show that application of mathematics in practice should be emphasised for the students of this speciality.Textual problem met in everyday life must be solved together with introducing economic, market concepts and laws.This is one of possibilities to improve professional training of primary school teachers in the field of mathematics.